Perilaku Banjir Kanal Barat dan Cengkareng Floodway serta kontribusinya terhadap fenomena banjir Jakarta (The Behavior of Cengkareng Floodway and Western Banfir Kenai and their Contributions to the Phenomenon of Jakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
River mouth is a river reach portion that has important role in the process of water (and sediment) migration from upstream towards downstream of the river. The presence of the river mouth and its corresponding behavior might influence drainage process, since its function as the final terminal might contribute considerable resistance to flow. The river mouth behavior may be affected considerably due to the hydrodynamic phenomenon at the surrounding river mouth, either natural or human interfere. This paper deals with the evaluation of the rise of water level elevation at the Cengkareng Floodway and Western Banjir Canal due to the change of their behavior, as well as their influences to the Jakarta flooding that might occur. Hydraulics routing by the application of one dimensional unsteady flow model is introduced throughout the study, i.e. by utilization of DUFLOW computer software. Series of simulations which assume various river mouth conditions, e.g. the reclamation in front of the river mouth (which is blamed as a big issue contributing Jakarta flooding) were carried out. The flood routing based on the presence of reclamation with the existing size of Western Banjir Canal and Cengkareng Floodway, and 2 years return period of flood hydrograph, causes 0.78 cm and 0.40 cm increase of water level elevation respectively. Similarly, a 100 years return period of flood hydrograph, causes 12.80 cm and 7.60 cm increase of water level elevation at the mouth of Western Banjir Canal and Cengkareng Floodway respectively. Although the increase of water level elevation is considerably small, the magnitude of the increase should be well compromised, whether or not negligible. Such matter has not been established yet, and need to be seriously taken into account in the Jakarta flooding countermeasure.